Recording Russia : trying to listen in the nineteenth century - Safran, Gabriella, 1967- (Cornell University Press, 2022)
"Nineteenth-century Russian writers including Dahl, Turgenev, and Dostoevsky, and travelers including Custine and Haxthausen, describe scenes where they and their characters listen to, record, and borrow other people's words. Drawing on linguistic anthropology and media studies, this book explores how these scenes index identities, reference communication technology, and change over time"--